2011
DOI: 10.1155/2012/168540
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Conditions of Extracellular Proteases Production from a Newly Isolated Streptomyces Pseudogrisiolus NRC‐15

Abstract: Microbial protease represents the most important industrial enzymes, which have an active role in biotechnological processes. The objective of this study was to isolate new strain ofStreptomycesthat produce proteolytic enzymes with novel properties and the development of the low-cost medium. An alkaline protease producer strain NRC-15 was isolated from Egyptian soil sample. The cultural, morphological, physiological characters and chemotaxonomic evidence strongly indicated that the NRC-15 strain represents a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 11 publications
(13 reference statements)
0
3
0
3
Order By: Relevance
“…Further the interaction between the surfactant and carbon source is of relevance, where, the lower level in the carbon source was balanced by higher levels of surfactant for the establishment of worthy protease activity. This might be due to the adsorbed surfactant film around the cell which decreased or increased permeability or enhanced the availability of important ions, which has a favorable effect on protease activity ( Mostafa et al, 2012 ). Thus, from the present study it can be concluded that protease production in B. pumilus can be improved by controlling the carbon source and surfactants and this interaction could only be well-understood by suitable RSM selection.…”
Section: Discussionmentioning
confidence: 99%
“…Further the interaction between the surfactant and carbon source is of relevance, where, the lower level in the carbon source was balanced by higher levels of surfactant for the establishment of worthy protease activity. This might be due to the adsorbed surfactant film around the cell which decreased or increased permeability or enhanced the availability of important ions, which has a favorable effect on protease activity ( Mostafa et al, 2012 ). Thus, from the present study it can be concluded that protease production in B. pumilus can be improved by controlling the carbon source and surfactants and this interaction could only be well-understood by suitable RSM selection.…”
Section: Discussionmentioning
confidence: 99%
“…For protease production, a 2% (v/v) inoculum was used in 500 mL (1:10 medium:flask volume ratio) at initial pH 7.0. The initial evaluation was carried out using basal media previously reported for protease production [17][18][19][20][21], as detailed in Table 1. Further evaluation was performed with different carbon (10 g L −1 glucose, sucrose, glycerol, fructose, maltose, lactose, galactose, cellobiose, starch, cane molasses) or nitrogen sources (10 g L −1 peptone, yeast extract, skim milk, NH 4 Cl, (NH 4 ) 2 SO 4 , casein hydrolysate, beef extract, urea, gelatin, casein) by substituting original C or N sources in the selected basal medium B for protease production.…”
Section: Protease Productionmentioning
confidence: 99%
“…Os grupos das proteases constituem o maior grupo de enzimas utilizadas industrialmente no mundo, movimentando a economia deste setor ativamente (PILLAI et al, 2011). Estas enzimas têm como função hidrolisar ligações peptídicas (LI et al, 2012) e podem ser obtidas de diferentes fontes, entretanto as proteases microbianas se destacam pela sua metabolização e baixo custo (AWAD et al, 2013;MOSTAFA et al, 2012).…”
Section: Introductionunclassified
“…Os grupos das proteases constituem o maior grupo de enzimas utilizadas industrialmente no mundo, movimentando a economia deste setor ativamente (PILLAI et al, 2011). Estas enzimas têm como função hidrolisar ligações peptídicas (LI et al, 2012) e podem ser obtidas de diferentes fontes, entretanto as proteases microbianas se destacam pela sua metabolização e baixo custo (AWAD et al, 2013;MOSTAFA et al, 2012).As amilases estão entre as mais importantes enzimas industriais, são aplicadas como aditivos em detergentes, indústrias de alimentos, fermentação, papel e têxtil, farmacêutica, médica e químico-analítica (PANDEY et al, 2000; SOARES et al, 2010).As enzimas lipolíticas catalisam a hidrólise de gorduras e óleos, são consideradas o terceiro maior grupo baseado no volume total de compras, onde o uso comercial foi estimado em um bilhão (JAEGER et al, 1999). Possuem diversas aplicações industriais, utilizadas como biocatalisadores ideais em química orgânica entre outros (TREICHEL et al, 2010;LOU et al, 2013;SHARMA; KANWAR, 2014).…”
unclassified